What's right and wrong to business? : a primer on business ethics - Gomez, Raphael (Manila : Sinag-Tala Pub, 2002)
Translation of: Etica empresarial ; teoria y casos, 3rd ed., 1999
Includes index.
Keywords: Business ethics